2004
DOI: 10.1007/s00330-004-2333-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT angiography in the assessment of a fetal origin of the posterior cerebral artery

Abstract: An uncommon cause of cerebral ischemia in the territory of the posterior cerebral artery (PCA) is the combination of a fetal origin of the PCA and atherosclerotic disease in the internal carotid artery. This study compared the accuracy of CTA with DSA in the assessment of a fetal origin of the PCA. Patients in whom an intracranial DSA and CTA had been performed were reviewed. A fetal origin was defined as a normal-sized patent posterior communicating artery (PCoA) with hypoplasia or aplasia of the ipsilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
(25 reference statements)
3
20
0
Order By: Relevance
“…However, even the small arterial vessels could be reliably delineated and discerned by our readers. This is in accordance with a recently published study that demonstrated the accuracy of CT angiography in discerning a fetal origin of the posterior artery as a potential thrombo-embolic pathway [19]. The relatively poor score of the cavernous sinus and the C2 segment of the ICA is probably due to the close topographical proximity to the osseous structures of the skull base and constitutes a typical limitation of CT angiography.…”
Section: Discussionsupporting
confidence: 88%
“…However, even the small arterial vessels could be reliably delineated and discerned by our readers. This is in accordance with a recently published study that demonstrated the accuracy of CT angiography in discerning a fetal origin of the posterior artery as a potential thrombo-embolic pathway [19]. The relatively poor score of the cavernous sinus and the C2 segment of the ICA is probably due to the close topographical proximity to the osseous structures of the skull base and constitutes a typical limitation of CT angiography.…”
Section: Discussionsupporting
confidence: 88%
“…Preserving techniques may also influence the caliber of vessels [4,13]. Additionally, external mea- The studies confirm that CTA is an accurate imaging technique for the evaluation of the structures of the CW [7,16]. It is highly sensitive and specific, except when it comes to detecting hypoplastic segments, where it has a rather low sensitivity [7].…”
Section: Discussionmentioning
confidence: 76%
“…It is highly sensitive and specific, except when it comes to detecting hypoplastic segments, where it has a rather low sensitivity [7]. Additionally, CTA allows for exact assessment of the presence of the foetal configuration of the posterior part of the circle [16]. The main limitations of this study correspond to those of imaging techniques in general and particularly to limitations of CTA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Selective visualization of 1 artery may hinder a fair interpretation in digital subtraction angiography due to the injection pressure, the absence of a temporal window hampers transcranial Doppler use in approximately 25% of patients, and flow-based magnetic resonance angiography techniques may not visualize nonfunctional but patent arterial segments. Multidetector row CT scanning allows consistent imaging of intracerebral arteries together with the carotid and vertebral arteries and thereby represents an excellent tool for imaging the anatomy of the circle of Willis [25]. …”
Section: Discussionmentioning
confidence: 99%